Mathematics teacher identity in a professional learning community: Paper Presented on the 2nd - 7th April 2013, Cape Town, South Africa - Chauraya, Million (MES 7, 2019)
Teacher identity has always been regarded as significant in research about teacher professional development, but has received little attention in research about professional learning communities. In this paper I discuss the relationship between teacher identity and professional learning communities through a study of two teachers. I show that participation in the professional learning community influenced shifts in both teachers’ identities, and in turn the teachers’ evolving identities explained their participation in the professional learning community. The results highlight the importance of paying attention to teacher identity in analyzing teacher learning and participation in a professional learning community.